Material platforms for spin-based photonic quantum technologies - Atature, Mete; Englund, Dirk; Vamivakas, Nick; Lee, Sang-Yun; Wrachtrup, Joerg (NATURE RESEARCH, 2018)
A central goal in quantum optics and quantum information science is the development of quantum networks to generate entanglement between distributed quantum memories. Experimental progress relies on the quality and efficiency of the light-matter quantum interface connecting the quantum states of photons to internal states of quantum emitters. Quantum emitters in solids, which have properties resembling those of atoms and ions, offer an opportunity for realizing light-matter quantum interfaces in scalable and compact hardware. These quantum emitters require a material platform that enables stable spin and optical properties, as well as a robust manufacturing of quantum photonic circuits. Because no emitter system is yet perfect and different applications may require different properties, several light-matter quantum interfaces are being developed in various platforms. This Review highlights the progress in three leading material platforms: diamond, silicon carbide and atomically thin semiconductors.
Keywords: SINGLE COLOR-CENTERS; NITROGEN-VACANCY CENTERS; SILICON-CARBIDE; COHERENT CONTROL; SPONTANEOUS EMISSION; VALLEY POLARIZATION; MAGNETIC-RESONANCE; CRYSTAL CAVITY; ELECTRON SPINS; WAVE-GUIDE